Improved photoelectrochemical performance of electrodeposited metal-doped BiVO4 on Pt-nanoparticle modified FTO surfaces. Issue 20 (3rd May 2016) - Gutkowski, Ramona; Peeters, Daniel; Schuhmann, Wolfgang
Abstract : Modification of the FTO substrate with Pt-core results in higher photoelectrochemical performance compared to films electrodeposited on bare FTO substrates. Abstract : The recombination of photogenerated electron–hole pairs is one of the main limiting factors of photoelectrocatalysts absorbing in the visible part of the solar spectrum. Especially for BiVO4 the slow electron transport to the back contact facilitates charge recombination. Hence, thin layers have to be used to obtain higher photocurrents which are concomitantly only allow low absorption of the incident light. To address this limitation we have modified FTO substrates with Pt-nanoparticles before electrodepositing BiVO4 . The Pt-nanoparticles decrease the overpotential for the electrodeposition of BiVO4, but more importantly they provide the basis for decreased charge recombination. Electrodeposited Mo-doped BiVO4 on Pt-nanoparticle modified FTO exhibits a substantially decreased recombination of photogenerated charge carriers during frontside illumination. Simultaneous co-doping of BiVO4 with two different metals leads to a substantial enhancement of the incident-photon-to-current efficiency (IPCE) during light driven oxygen evolution reaction. Highest IPCE (>30% at 1.2 V vs. RHE) values were obtained for Mo/Zn- and Mo/B-doped BiVO4 .